Exploring causality between economic growth and air transport demand for Argentina and Uruguay. Issue 4 (2018) - Brida, Juan Gabriel; Monterubbianesi, Pablo Daniel; Zapata-Aguirre, Sandra
This paper investigates the effects in the long-term between air transportation and the economic growth in Uruguay and Argentina. Employing annual data from 1970 to 2011, the study uses cointegration analysis to consider the existence of a long-run relation between real GDP and the number of air passengers in each country. Results show that for both considered countries, the series are cointegrated and it is possible to estimate an error correction model (ECM). The Granger causality test shows that causality goes unidirectionally from GDP to air-transport for both countries. The elasticity and impulse-response function analysis shows that the effect of a GDP shock on the number of passengers is higher in Uruguay than in Argentina, which is consistent with the characteristics of the air market and the geographical conditions of each country. The results suggest different policy and planning implications.